THE LEGAL POSITION OF DEPUTY REGIONAL LEADER IN THE IMPLEMENTATION OF REGIONAL GOVERNMENT - Alwi Jaya; Gustika Sandra; Tarmizi Tarmizi; Asia Asia (Publikasi Indonesia, 2023)
The regulation of the legal position of Deputy Regional Heads in the implementation of Regional Government has undergone dynamics. Law Number 32 of 2004 has further clarified the position of Deputy Regional Heads in a more concrete manner. Especially with the election of a single pair with the Regional Head, it shows that the role of the Deputy Regional Head is becoming stronger in the implementation of Regional Government. This research uses a descriptive juridical method. The results of this study show that the regulation of the position and duties of deputy regional heads in the structure of regional government has undergone different regulatory dynamics in several laws. Their position as a local government official elected directly by the people as a running mate with the regional head strengthens their position in the structure of regional government. Although their duties are primarily to assist the regional head in the implementation of regional government, in certain situations, the deputy regional head can replace the regional head when the regional head is unable to perform their duties.